Application of novel and green technology in industry - Gholamrezaei, Afshin; Shabbooei, Ahmad Reza; Ghaferin, Sanaz Alsadat (International journal of industrial engineering and operational research, 2023)
The industrial sector plays a significant role in driving economic growth and meeting the needs of society. However, traditional industrial practices have often been associated with adverse environmental impacts, including pollution, resource depletion, and carbon emissions. To address these challenges, there has been a growing emphasis on the application of novel and green technologies in industrial processes. This paper explores various innovative technologies that are transforming industries towards more sustainable and environmentally friendly practices. It discusses the benefits, challenges, and potential future developments of these technologies.